Project Veeartsenijschool. - De Buck, Noel (Gent : Koninklijke Academie voor Schone Kunsten Hogeschool Gent, 1999)
Anseel, Stijn ; Baeckelandt, Peter ; De Bakker, Ilse ; Beck, Ingeborg ; Begijn, Lisandre ; Van Belle, Tom ; De Beuckelaere, Lieva ; Bicherdyke, Dona ; Bijnens, René ; Blankaert, Katrien ; Blockeel, Cindy ; De Bodt, Nora ; Bogaert, Benedict ; Bogaert, Els ; Bourgeois, Renaat ; Bruggeman, Peter ; De Buysere, Saat ; Callaert, Yves ; Carlier, Nele ; Ceulemans, Els ; Claeys, Karin ; Collet, Bruno ; Colpaert, Kristof ; Cottenier, Henk ; Cottenier, Joost ; Cox, Wouter ; De Craene, Laurence ; D'Haluin, Bart ; D'Heedene, Stefaan ; D'hondt, Klaas ; D'Hondt, Lieve ; Debruycker, Jibbe ; Dedoncker, Tom ; Demoor, Sylvie ; Deseyne, Tom ; Desmet, Peter ; Dierickx, Jo ; Druart, Brigitte ; Dumortier, Daniel ; Duyck, Kurt ; Van Elslander, Nicolas ; Gabriël, Bart ; Geerinck, Katlene ; De Geeter, Barbara ; Gentils, Paul ; Gevaert, Jeroen ; Van Ghillewe, Jolien ; Goemaere, Kirsten ; Goetinck, Lieven ; Goetinck, Pierre ; Goffin, Mieke ; Grahovac, Goran ; Guthörel, Frank ; Heller, Charlotte ; Hermans, Ward ; Jacquemyn, Jonathan ; Joye, Alexander ; Kerfs, Inge ; Kimpe, Stephane ; Knoudlbach, Hans ; Kratky, Friederike ; Lapeire, Roos ; Laureys, Anne Marie ; Lippeveld, Kris ; Louvaert, Pascal ; Maes, Annemie ; De Maeyer, Mieke ; Mahieu, Anique ; Marion, Gunther ; Marion, Otto ; Matsumoto, Yoshimasa ; Merchant, Peter ; Messiaen, Steven ; Mike ; Neirings, David ; Van Paemel, Ellen ; Parmentier, Ignace ; Pay, Frank ; Pée, Iwe ; Penninckx, Lucia ; Philips, Koen ; Piccu, Lynn ; Piteraerents, Wout ; De Poorter, Koen ; De Rouck, Ann ; Ryssaert, Chris ; Seynaeve, Andy ; Soenen, Gobijn é ; Soens, Karen (& Bart) ; Spapens, Fon ; De Staercke, Steven ; Van Stapele, Nicoline ; De Strooper, Pedro ; Strynck, Frank ; Sturtewagen, Tim ; Tanaquil, Berto ; Tas, Dirk ; Troch, Griet ; etc.
Nederlands
boek